Regulatory effect of N6-methyladenosine on tumor angiogenesis - YuYan,; Yuan, Enwu (Frontiers in Immunology, 2024)
Previous studies have demonstrated that genetic alterations governing epigenetic processes frequently drive tumor development and that modifications in RNA may contribute to these alterations. In the 1970s, researchers discovered that N6-methyladenosine (m 6 A) is the most prevalent form of RNA modification in advanced eukaryotic messenger RNA (mRNA) and noncoding RNA (ncRNA). This modification is involved in nearly all stages of the RNA life cycle. M 6 A modification is regulated by enzymes known as m 6 A methyltransferases (writers) and demethylases (erasers). Numerous studies have indicated that m 6 A modification can impact cancer progression by regulating cancer-related biological functions. Tumor angiogenesis, an important and unregulated process, plays a pivotal role in tumor initiation, growth, and metastasis. The interaction between m 6 A and ncRNAs is widely recognized as a significant factor in proliferation and angiogenesis. Therefore, this article provides a comprehensive review of the regulatory mechanisms underlying m 6 A RNA modifications and ncRNAs in tumor angiogenesis, as well as the latest advancements in molecular targeted therapy. The aim of this study is to offer novel insights for clinical tumor therapy.